2013
DOI: 10.1538/expanim.62.49
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Prolactin Receptor Gene Expression in the Rat Choroid Plexus via Transcriptional Activation of Multiple First Exons during Postnatal Development and Lactation

Abstract: Prolactin (PRL) has numerous physiological functions that are mediated by its receptors in target cells. Expression of the rat PRL receptor (PRLR) gene is regulated in a tissue-specific manner via the transcriptional activation of five distinct first exons, i.e., E1 1 , E1 2 , E1 3 , E1 4 , and E1 5 . In the present study, we investigated the expression profiles of these first exon variants of PRLR mRNA in the rat choroid plexus, which is considered to be a site of receptor-mediated PRL transport from the bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Thus, although serum PRL levels remain increased following continuous sexual behavior, the impact on the prostate is transient. It is known that increased serum PRL results in increased PRL receptor levels at the choroid plexus [24], and we observed the same pattern for prostate receptor mRNA in this study. However, although serum PRL levels remained high, the level of prostate receptor mRNA decreased in the long-term.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, although serum PRL levels remain increased following continuous sexual behavior, the impact on the prostate is transient. It is known that increased serum PRL results in increased PRL receptor levels at the choroid plexus [24], and we observed the same pattern for prostate receptor mRNA in this study. However, although serum PRL levels remained high, the level of prostate receptor mRNA decreased in the long-term.…”
Section: Discussionsupporting
confidence: 88%
“…Although PRL is expressed in the CNS, mainly in hypothalamic neurons [5], Larsen and Grattan [28 ]demonstrated that inhibition of pituitary PRL secretion by bromocriptine increased postpartum anxiety and impaired maternal behavior, and that subcutaneous PRL administration restored the normal maternal behavioral patterns. In fact, PRL enters the brain via the choroid plexus by a PRLR-mediated mechanism, and it was shown that the expression of PRLR in choroid plexus increased during lactation [29]. These observations suggest that PRL effects at the CNS level are mainly exerted by PRL secreted by the pituitary gland.…”
Section: Prolactin Actions In the Hypothalamusmentioning
confidence: 99%
“…Information regarding the physiological and genomic regulation of PRLR expression in vivo has mostly stemmed from data for rodents (Hu et al 1996, 1998, Tabata et al 2012, Hirai et al 2013, or has specifically focused on PRLR expression in cancer cells in vitro and the response to stimulation by ovarian hormones (Hu et al 2002, Dong et al 2006. More than one promoter has been identified within the PRLR gene of mice (Ormandy et al 1998), rats (Hu et al 1998) and humans (Hu et al 2002), although limited data exist regarding the activity of these known first exon promoters in different tissues from these species.…”
Section: Introductionmentioning
confidence: 99%